Predictors of clinical outcome in post-thrombolysis among sample of Egyptian patients with acute ischemic stroke - AbdelRahman Mohamed Hussein; Iman Mohamed Bayoumy; Khaled Ossama Abdulghani; Mona Ali Eissa; Ehab Mostafa Ahmed; Ali Ahmed Abou Elmaaty (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Stroke stands as a major cause of morbidity and mortality worldwide. The recommended treatment for eligible patients within the initial 4.5-h window is intravenous recombinant tissue plasminogen activator (IV rt-PA). This study explored the factors influencing functional outcome following IV rt-PA treatment in a group of Egyptian patients with acute ischemic stroke (AIS). We included sixty patients diagnosed with AIS who met the criteria for IV rt-PA therapy. Data were collected and statistically analyzed, we established correlations with functional outcomes as measured by the modified Rankin Scale (mRS) and National Institute of Health Stroke Scale (NIHSS) 3-month post-treatment. Results Of the 60 patients, 40 (66.67%) exhibited a favorable functional outcome, while 20 (33.33%) experienced a less favorable outcome. Poor functional outcome was associated with atrial fibrillation [p value < 0.001, odds ratio (OR) 6.28], hypertension (p value = 0.001, OR 3.65), diabetes mellitus (p value 0.009, OR 2.805), and a higher NIHSS at admission (p value = 0.003, OR 8.03). Conclusions Certain factors may affect functional outcome in stroke patients treated with rt-PA therapy. There are strong associations between hypertension, diabetes, atrial fibrillation, post-rt-PA intracerebral hemorrhage (both asymptomatic and symptomatic), specific stroke subtypes, and less favorable functional outcome 3 months after rt-PA administration, as measured by the mRS.